The Fall of the Moghul Empire of Hindustan - Keene, H. G. (Lahore Al-Biruni, 1975)
he Mughal, or Moghul, Empire ruled much of the Indian subcontinent (archaically called 'Hindustan') for 3 centuries, finally falling in the mid-19th century. This is a fantastic and comprehensive account of the last years of the Empire and its fall, one of the most important events in Indian history.
Include Appendices and Index.
The full name of author is Henry George Keene. He is also author of "The History of Hindustan."
Keywords: India--Moghul Empire -- India -- Moghul Empire -- Mughal Empire -- Mughal Empire--Hindustan -- Moghul Empire--Hindustan